Trust the crowd: Crowdsourced fact-checking is as effective at reducing confidence in misinformation as expert fact-checking - Cindy Phan Vu; Lauren L. Saling (PLoS ONE, 2026)
The rapid spread of misinformation on social media has created significant challenges for expert fact-checking initiatives to counter in a timely and effective manner. Misinformation undermines behaviour and decision-making in many spheres including health and political domains. X (formerly known as ‘Twitter’) utilises crowdsourced fact-checking (termed ‘Community Notes’) to manage the high volume of and engagement with online misinformation. Community Notes have also been introduced to mitigate perceived partisanship and bias of expert fact-checkers. The present study recruited 102 participants to investigate whether expert or crowdsourced fact-checks on X are more effective at reducing belief in misinformation and engagement with misinformation. Participants were randomly allocated into either an expert or crowdsourced fact-checking condition. Confidence in the veracity of misinformation and willingness to retweet were measured, before and after exposure to fact-checks. It was found that both crowdsourced and expert fact-checks reduced confidence in misinformation and willingness to retweet the information. The results demonstrate the efficacy of crowdsourced fact-checking, a fact-checking variant that is rapidly gaining popularity. Given this, the adoption of crowdsourced fact-checking by other social media platforms warrants consideration.